The role of the police in disaster management - Fraser, Mary (Policing and society, 2025)
This article shows the conditions under which the police in Britain manage national and local disasters by working closely with those providing a service to alleviate the situation, both today and in previous times. I compare the work of the police in two periods beginning with the present: the 2021 COVID-19 disaster related to the London and the South Western ambulance services, compared with food insecurity in the last two years of the First World War, to demonstrate how the police in both eras managed the population while helping to provide an essential service. Both examples convey that helping the population and communities during disasters is a legitimate role for the police which helps to maintain public order and brings them closer to the communities they serve, thereby increasing the credibility of policing by consent. Police involvement in disaster management today while tracing its roots to similar conduct in an earlier time, highlights the changes in the social and cultural context of policing. Following today’s practices back in time foregrounds the present in the context of the past.